The Effect of Work-Life Balance and Emotional Intelligence on Job Satisfaction of K-24 Pharmacy Employees in Jayapura City - Dwi Abdur Rouf; Yasir Attamimi (Publikasi Indonesia, 2024)
The Effect of Work-life Balance and Emotional Intelligence on Job Satisfaction of K-24 Pharmacy Employees in Jayapura City. Management Study Program, Department of Management, Faculty of Economics and Business, Cenderawasih University. The objectives of this study are: 1) To find out and analyze whether work-life balance and emotional intelligence simultaneously affect the job satisfaction of K-24 pharmacy employees in Jayapura city; 2) To find out and analyze whether work-life balance and emotional intelligence partially affect the job satisfaction of K-24 pharmacy employees in Jayapura city; 3) To find out and analyze which variables between work-life balance and emotional intelligence are more dominant in influencing the job satisfaction of K-24 pharmacy employees in Jayapura city. This type of research is quantitative research. The population in this study is all employees of K-24 pharmacies in the city of Jayapura which totals 81 employees. The number of samples is determined using the total sampling technique, which is the number of samples equal to the number of populations. Data analysis using multiple linear regression with the help of the SPSS version 23 program. The results of the study showed: 1) There was a simultaneous influence of work-life balance and emotional intelligence variables on the job satisfaction of K-24 pharmacy employees in Jayapura city; 2) There is a partial influence of work-life balance and emotional intelligence variables on the job satisfaction of K-24 pharmacy employees in Jayapura city; 3) The variable emotional intelligence is a more dominant variable that affects the job satisfaction of K-24 pharmacy employees in Jayapura city.